2004
DOI: 10.1038/ng1296
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evidence for impaired AKT1-GSK3β signaling in schizophrenia

Abstract: Alterations in intracellular signaling pathways are important in treating complex neuropsychiatric disorders 1 . Signaling pathway components, including several protein kinases and phosphatases, are direct targets of some of the most effective medications for treating these disorders. For example, lithium, one of the most established treatments for bipolar disorder (BPD), is believed to exert its therapeutic effects by directly modulating the activity of inositol monophosphatase and of glycogen synthase kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
855
14
17

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 870 publications
(953 citation statements)
references
References 31 publications
56
855
14
17
Order By: Relevance
“…Additionally, we probed all blots for b-Tubulin, which was used as internal lane loading control. b-Tubulin has previously been used as internal control 52,53 and several studies have found expression of b-Tubulin to be unaffected in schizophrenic brain. 54,55 However, in order to further minimize the potential effect of dendritic loss on bTubulin expression, we used an antibody that recognizes not only the neuron-specific isoform III, but all b-Tubulin isoforms (I, II, III, IVa and IVb), representing both neuronal and non-neuronal tubulin expression.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we probed all blots for b-Tubulin, which was used as internal lane loading control. b-Tubulin has previously been used as internal control 52,53 and several studies have found expression of b-Tubulin to be unaffected in schizophrenic brain. 54,55 However, in order to further minimize the potential effect of dendritic loss on bTubulin expression, we used an antibody that recognizes not only the neuron-specific isoform III, but all b-Tubulin isoforms (I, II, III, IVa and IVb), representing both neuronal and non-neuronal tubulin expression.…”
Section: Resultsmentioning
confidence: 99%
“…Akt is a serine/threonine kinase that regulates cell growth, glucose uptake, metabolism, and increases cell survival. A reduction in Akt levels in the frontal cortex and hippocampus of schizophrenic patients (Emamian et al, 2004) may be connected with neurodegenerative changes observed in this illness. Activated Akt phosphorylates many intracellular substrates, for example, it phosphorylates the GSK-3b at Ser9 and inactivates it.…”
Section: Discussionmentioning
confidence: 98%
“…17,20 Several researches have reported that abnormalities of neural cell adhesion, neuronal function, and Wnt/Wingless exist in schizophrenia. [10][11][12][13][14][15]18,19,[23][24][25][26] Third, APC is located at 5q21-22, which has been previously reported to be linked with schizophrenia. 27,28 Three SNPs of APC are associated with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recently, evidences for potential disturbances of Wnt signaling pathways in schizophrenia have accumulated. [10][11][12][13][14][15] However, as far as the authors are aware, the involvement of APC in schizophrenia has not been reported. The immunoprecipitation experiment results suggested that APC is involved in cell adhesion.…”
mentioning
confidence: 96%